2014
DOI: 10.5194/bg-11-425-2014
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to project DUNE, a DUst experiment in a low Nutrient, low chlorophyll Ecosystem

Abstract: International audienceThe main goal of project DUNE was to estimate the impact of atmospheric deposition on an oligotrophic ecosystem based on mesocosm experiments simulating strong atmospheric inputs of eolian mineral dust. Our mesocosm experiments aimed at being representative of real atmospheric deposition events onto the surface of oligotrophic marine waters and were an original attempt to consider the vertical dimension after atmospheric deposition at the sea surface. This introductory paper describes the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 80 publications
(108 reference statements)
1
61
0
1
Order By: Relevance
“…This sampling strategy was chosen to minimize the effect of zooplankton catches on the plankton abundance and composition in the mesocosms. Guieu et al (2010) and Guieu et al (2014) have performed several mesocosm experiments in the Mediterranean Sea and demonstrated that the type of mesocosms used in the present study is well adapted to conduct replicated process studies on the first levels of the pelagic food web in LNLC environments. In order to evaluate the reproducibility among the three mesocosms deployed during VAHINE, we calculated the coefficient of variation (CV, %) of the main stocks and fluxes measured every day for 23 days for every sampling depth (Table 1; the methods are described in detail in the publications making up this special issue).…”
Section: Logistics and Sampling Strategymentioning
confidence: 98%
See 1 more Smart Citation
“…This sampling strategy was chosen to minimize the effect of zooplankton catches on the plankton abundance and composition in the mesocosms. Guieu et al (2010) and Guieu et al (2014) have performed several mesocosm experiments in the Mediterranean Sea and demonstrated that the type of mesocosms used in the present study is well adapted to conduct replicated process studies on the first levels of the pelagic food web in LNLC environments. In order to evaluate the reproducibility among the three mesocosms deployed during VAHINE, we calculated the coefficient of variation (CV, %) of the main stocks and fluxes measured every day for 23 days for every sampling depth (Table 1; the methods are described in detail in the publications making up this special issue).…”
Section: Logistics and Sampling Strategymentioning
confidence: 98%
“…1) is sea-going mesocosms which are entirely transportable and which can be used under low to moderate wind and wave conditions (20-25 kn, 2.5 m wave height). They have been designed in the frame- work of the DUst experiment in a low Nutrient, low chlorophyll Ecosystem (DUNE) project (Guieu et al, 2010;Guieu et al, 2014) and consist of large transparent bags made of two 500 µm thick films of polyethylene (PE) and ethylene-vinyl acetate (EVA, 19 %), with nylon meshing in between to allow maximum resistance and light penetration (produced by HAIKONENE KY, Finland) (Fig. 2).…”
Section: Mesocosms Description and Deploymentmentioning
confidence: 99%
“…By design these experiments often integrate valuable series of joint and parallel measurements, yielding detailed data from various scientist with different expertise (e.g. Williams and Egge, 1998;Riebesell et al, 2008;Guieu et al, 2014). Drawbacks are uncertainties in initial conditions and also the representativeness of mesocosm data to reflect the real dynamics in the ocean is subject to discussion (e.g.…”
Section: Constraining Simulations Of Algal Growth With Laboratory Andmentioning
confidence: 99%
“…Briefly, the mesocosms used in this study (volume of ∼ 52 m 3 ) were fully described in Guieu et al (2014). The mesocosms consisted of large bags made of two 500 µm thick films of polyethylene mixed with vinyl acetate (EVA, 19 %) with nylon meshing in between to allow maximum resistance and light penetration (Haikonene KY, Finland).…”
Section: Measurement Sites and Campaignsmentioning
confidence: 99%